Los usos de la motivación en el acto administrativo: un análisis crítico de sus exigencias argumentativas básicas - Celis Vela, Dúber Armando (2025)
The constitutional state is considered a model that presupposes higher argumentative demands in applying legal norms. In legal culture, studies on this matter are focused on justifying judicial decisions. The theoretical attention to the argumentative issues of administrative acts has been relatively less. This article aims to analyze the uses of motivation that seem established in administrative-legal practice concerning administrative acts. The methodology applied is theoretical analysis and critical evaluation of relatively shared argumentative practices. The text argues that conceptions of argumentation and the use of reasons in issuing an administrative act warrant more stringent standards of justification for a decision that impacts the rights and obligations of the governed.